Estudio de prefactibilidad para la instalación de una planta productora de barras energéticas a base de cacao (Theobroma cacao) y chía (Salvia hispanica) - Jaramillo Enciso, Ronald Antony (2023)
The present pre-feasibility project for the elaboration of energy bars based on cocoa and chia, it was motivated by the increase in people who have changed a sedentary lifestyle to a healthy one, since the increase in obesity, diabetes, and other diseases related to poor diet, have affected people in a detrimental way. The main product is cocoa with chia that will be baked and vacuum packed, which will allow it to be kept in optimal conditions for consumption. In the macro-location study, it was determined that the company will be located in the department of Lima and in the micro-location it was determined that the plant will be located in the district of Ate, these locations will allow optimizing logistics both the delivery of the final product and the obtaining the raw material and inputs required for production. This project will have 4 machines and 15 people for the production and administrative process. This project has a production program of 495 794 units and an area of 531,56 m2. The company will be register with the name INDUSTRIA SALUD SAC (closed stock company). The project has a VNA of S/ 330 402,28, a TIR of 51% and a recovery period of 2 years, 2 months, and 26 days, this highlights that it is a sustainable and viable project that requires an investment of S/ 310 805,60 both in tangibles and intangibles.